PENGARUH KEPEMIMPINAN, KOMUNIKASI INTERNAL, DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI BP3AKB PROVINSI JAWA TENGAH - Ardilla, Niken Dwi; Pramusinto, Hengky (Dinamika Pendidikan, 2015)
The purpose of this research is to find out whether there is an influence of leadership, internal communication, and work motivation to the Department of Women's Empowerment, Child Protection and Family Planning in Central Java either simultaneously or partially. The population in this research are 87 employees in the Department of Women's Empowerment, Child Protection and Family Planning in Central Java. The research methods used in this study were interview, questionnaire and documentation. The analysis data used in this study were descriptive analysis percentage and multiple linear regression analysis with SPSS for Windows release 16. The results of the regression equation: Y = -0448 + 0.320X1 + 0.518X2 + 0.242X3 with Y (employee performance), X1 (leadership), X2 (internal communication), and X3 (work motivation). The results of this study that there is influence between leadership, internal communication and work motivation to employee performance was 51,4%. Partially, the influence of leadership (X1) on Y by 0.320 with a value by 10.63% partial relations at the significance level of 0.002, while the influence of internal communication (X2) to Y of 0.518 with 10.17% for partial relations at the significance level of 0.003, and the influence of work motivation (X3) to Y with values of 0.242 relations partially by 10.17% at the significance level of 0.003.